Structures of sialylated fucosyl polylactosaminoglycans isolated from chronic myelogenous leukemia cells. - Fukuda,M; Bothner,B; Ramsamooj,P; Dell,A; Tiller,PR; Varki,A; Klock,JC (J Biol Chem, 1985)
Polylactosaminoglycans were isolated from human chronic myelogenous leukemia cells and their structures were elucidated. The lactosaminoglycan saccharides were isolated by hydrazinolysis and fractionated by QAE-Sephadex. The structures of fractionated oligosaccharides were analyzed by fast atom bombardment-mass spectrometry and methylation before and after treatment with specific exoglycosidases, such as alpha 2----3 specific neuraminidase. Based on these experiments, the structures of sialyl polylactosaminoglycans of chronic myelogenous leukemia cells were found to contain the following unique structure which is absent in normal mature granulocytes: (formula; see text) In addition to this, chronic myelogenous leukemia polylactosaminoglycans can be distinguished from normal granulocyte polylactosaminoglycans by the following characteristics. Leukemic polylactosaminoglycans are (a) shorter, (b) more highly sialylated and contain fully sialylated, tetrasialosyl polylactosaminoglycans, (c) are less fucosylated at C-3 of N-acetylglucosamine of polylactosaminyl side chains, and (d) contain a significant amount of sialyl Lex, NeuNAc alpha 2----3Gal beta 1----4(Fuc alpha 1----3)GlcNAc beta 1----3, structure. These results indicate that chronic myelogenous leukemia cells express unique polylactosaminoglycan structures which are distinct from normal mature granulocytes.